2016
DOI: 10.1590/1234-56781806-94790540308
|View full text |Cite
|
Sign up to set email alerts
|

Pobres no Campo, Ricos na Cidade? Uma Análise Multidimensional da Pobreza

Abstract: Resumo: O objetivo deste trabalho é identificar se existe uma relação entre os níveis de pobreza rural e urbano. Para isso, primeiramente foi auferido o patamar de pobreza para ambos os espaços, baseado na definição de pobreza multidimensional, admitindo, portanto, que as carências em saúde, renda, educação e moradia são componentes fundamentais para mensuração das privações. A abordagem utilizada para o indicador de pobreza multidimensional foi a lógica fuzzy, enquanto que a análise de dependência entre os in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Most papers only created the area-level measure of deprivation for specific areas (e.g., states, regions, cities) within Brazil and not for the entire country. Three papers created their measure for the whole of Brazil; Costa et al and Cortellazzi et al used the municipality area-level 52 , 53 and Barros et al used the Regions and States 54 ; none of them was at the census tract level. Costa et al and Cortellazzi et al used data from 2010 Census 52 , 53 , Barros et al used data from 1991 and 2000 Census 54 .…”
Section: Resultsmentioning
confidence: 99%
“…Most papers only created the area-level measure of deprivation for specific areas (e.g., states, regions, cities) within Brazil and not for the entire country. Three papers created their measure for the whole of Brazil; Costa et al and Cortellazzi et al used the municipality area-level 52 , 53 and Barros et al used the Regions and States 54 ; none of them was at the census tract level. Costa et al and Cortellazzi et al used data from 2010 Census 52 , 53 , Barros et al used data from 1991 and 2000 Census 54 .…”
Section: Resultsmentioning
confidence: 99%
“…Por fim, apesar das mudanças, constata-se maior proporção de municípios com alto IPM nas regiões Norte e Nordeste e com baixo IPM nas regiões Sul e Sudeste. Costa & Costa (2016) utilizaram os dados do Censo Demográfico de 2010 para analisar os municípios brasileiros e observaram que, embora as políticas públicas atinjam da mesma forma os indivíduos das áreas urbanas e rurais, elas produzem os melhores resultados nas áreas urbanas, sugerindo que as especificidades de cada localidade devem ser incorporadas para um maior êxito na redução das privações.…”
Section: Fundamentação Teóricaunclassified
“…Lastly, in spite of the changes, there was higher number of cities with elevated MPR in the North and Northeast of the country and low MPR in the South and Southeast regions. Costa & Costa (2016) used data from Brazilian Demographic Census from 2010 to analyze Brazilian cities and observed that, although public policies reach individuals from urban and rural areas the same way, they produce better results in urban areas; it suggests that the characteristics of each place should be incorporated for greater success in reducing deprivations. Silva et al (2017b) observed in their study higher proportion of multidimensional poverty for the North of Brazil from 2006 to 2013.…”
Section: Theoretical Foundationsmentioning
confidence: 99%